2008
DOI: 10.1111/j.1442-2050.2007.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hemoglobin level on survival in definitive chemoradiotherapy for T4/M1 lymph node esophageal cancer

Abstract: We retrospectively investigated the impact of the pre-chemoradiotherapy hemoglobin level (pre-CRT Hb level) for T4 and/or M1 lymph node (LYM) squamous cell carcinoma of the esophagus. Chemotherapy consisted of protracted infusion with 5-fluorouracil (5-FU) at 400 mg/m(2)/day on days 1-5 and 8-12, combined with cisplatin at 40 mg/m(2)/day on days 1 and 8, repeated twice at a 5-week interval. Concurrent radiation therapy was started on day 1 and delivered at 2 Gy/day for five days a week for a total radiation do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…The prognostic significance of low pretreatment anemia has previously been investigated in various cancers; low Hb is associated with poorer outcomes in many types of human cancer, particularly in HN cancers and gynecological tumors . A positive relationship between survival outcomes and Hb levels has been demonstrated in patients with NPC receiving RT ± chemotherapy: low pretreatment Hb was related to increased risk of death or metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic significance of low pretreatment anemia has previously been investigated in various cancers; low Hb is associated with poorer outcomes in many types of human cancer, particularly in HN cancers and gynecological tumors . A positive relationship between survival outcomes and Hb levels has been demonstrated in patients with NPC receiving RT ± chemotherapy: low pretreatment Hb was related to increased risk of death or metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…In a multivariate analysis, anemia was identified as a highly significant prognostic factor for 2-year OS and 2-year DFS, independent of TNM stage and initial treatment. Zenda and colleagues [12] concluded that the pre-chemoradiotherapy hemoglobin level may be an important determinant of outcome in patients with T4/M1 LYM squamous cell carcinoma of the esophagus. This result was consistent with previous studies regarding anemia.…”
Section: Discussionmentioning
confidence: 99%
“…These include a small study of 48 patients with T4/M1 SCC oesophageal cancer who were treated with chemoradiotherapy. 13 Pre-treatment haemoglobin of <13 g/dl was associated with a prognostic hazard ratio of 0.45 (p=0.04). A large study of 243 patients with SCC undergoing chemoradiotherapy found that 60 were anaemic and the five-year survival was significantly reduced in the anaemic group (p=0.001).…”
Section: Discussionmentioning
confidence: 97%